2019
DOI: 10.1021/acssuschemeng.9b05008
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effects of Paraffin Wax on Interactions between Polyphosphoric Acid and Bitumen Constituents

Abstract: Despite the merits of using polyphosphoric acid (PPA) in modification of bitumen, its desirable stiffening effect on bitumen is totally composition-dependent. While asphaltenes and resins are correctly introduced as the immediate components affected by PPA, our laboratory rheological investigations show that bitumen's wax content could be a potential interference for PPA's modification function. As evidenced by the complex viscosity test, PPA is very effective in low-wax bitumen, but its effect on high-wax bit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Therefore, nondirectional longrange electrostatic forces are the driving forces for the association of PPA-resin into pairs. Based on our energy decomposition analysis (EDA) results, 10 in addition to a significant electrostatic interaction (70.5%), an ion-pair of PPA-quinoline takes advantage of the orbital mixing interactions (22.4%) arising from charge donation−acceptation interactions between two fragments.…”
Section: ■ Materials and Methods In Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, nondirectional longrange electrostatic forces are the driving forces for the association of PPA-resin into pairs. Based on our energy decomposition analysis (EDA) results, 10 in addition to a significant electrostatic interaction (70.5%), an ion-pair of PPA-quinoline takes advantage of the orbital mixing interactions (22.4%) arising from charge donation−acceptation interactions between two fragments.…”
Section: ■ Materials and Methods In Experimentsmentioning
confidence: 99%
“…Another reason could be possible antagonism between PPA’s function and that of other bitumen modifiers. Considering the acidic nature of PPA, there has always been a concern about PPA’s probable reaction with basic antistripping agents such as lime and amines, which are commonly used in moisture-control additives. , The possible adverse reactions are not limited to PPA’s interaction with other bitumen additives; our recent studies on the rheological properties of PPA-modified bitumen show that the wax content of the bitumen could be a potential interference for PPA’s modification function. , Other laboratory evaluations conducted on warm-mix bitumen-containing PPA have also indicated that the low-temperature properties of bitumen are impaired. , Also contributing to the uncertainty in PPA application are some unknowns or perceived consequences associated with PPA in the long term; the most important of these is the hydrophilic nature of PPA, which causes moisture susceptibility of PPA-modified bitumen.…”
Section: Introductionmentioning
confidence: 99%
“…Bitumen is a colloidal mixture that consists of large molecules called asphaltenes in the discrete phase and saturates, aromatics, and resins in the continuous (liquid) phase of bitumen. 139 The resins-to-asphaltenes ratio in bitumen is a determinative factor in bitumen characteristics. 140 If the ratio of a mixture falls off toward the pure maltene, the mixture shows a solution behavior; if most of the mixture is asphaltenes, the mixture is in gelatinous form.…”
Section: Chemical Agingmentioning
confidence: 99%
“…Aging affects the chemical composition of bitumen. Bitumen is a colloidal mixture that consists of large molecules called asphaltenes in the discrete phase and saturates, aromatics, and resins in the continuous (liquid) phase of bitumen . The resins-to-asphaltenes ratio in bitumen is a determinative factor in bitumen characteristics .…”
Section: Chemical Agingmentioning
confidence: 99%
“…24 In this case, the effect of modifiers of paraffin crystals depends on the oil composition, 25 and asphaltenes can interfere with the action of inhibitors. Apparently, the details of the interaction of paraffin with molecules of other types can be clarified only using the methods of molecular dynamics and quantum chemistry, 26,27 considering it at the molecular level, relying on the experimental data of adequate in situ methods.…”
Section: ■ Introductionmentioning
confidence: 99%